Educational videos with nutritional approach in YouTube - DAUN, Felipe; Dianezi GAMBARDELLA, Ana Maria (Revista de Nutrição, 2023)
Objective Produce food and nutrition education videos, post these on YouTube and evaluate their reception over a two-year period. Methods Afterward bibliographic searches, sixteen different themes were developed and explored. An educational objective was defi ned for each video, took into account food and nutrition aspects in Brazil. The reception of the videos was evaluated using the “YouTube Analytics” tool, which allows analysis of the number of times videos were played, average playing time, and profi le of the viewers. Results Sixteen videos were produced from November 2013 to July 2015. Views for each video within two years of posting were calculated individually, giving a total of 78,546 views for all videos. Most of the videos delivered their educational message before the audience lost interest. Conclusion Videos successfully reached the YouTube users and delivered the food and nutrition education messages. Therefore, this pioneering work showed YouTube as a new setting for health promotion in Brazil, paving the way for further initiatives with this platform.